Bioconversion of coconut-residue to soluble protein by Aspergillus awamori - Aizat Mohd-Razali,; Mariam Taib,; Masouki Murni,; Aziz Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Protein is the most expensive and important nutrient component in feed formulation. An alternative protein source should be employed to reduce the dependency on fish meal. Limited reports are available regarding the bioconversion of coconutresidue derived-carbohydrate to soluble protein. The objective of this study was to determine the soluble protein and amino acid contents of coconut-residue after solid-state-fermentation by Aspergillus awamori. The complete randomised design (CRD) with three parameters; the inoculum-size (10%, 20%, and 30%), incubation temperature (30°C, 35°C and 40°C) and salt concentration (1x, 2x, 3x) were tested. Response surface method (RSM) was used to optimise the fermentation conditions. As a result, fermentation was increased and showed that the soluble protein content of the coconut-residue, to be 1.13-folds higher than the control. RSM analysis displayed that the best fermentation conditions comprised of 21.29% of inoculum size, 34.39°C of incubation temperature and 2.7-times of salt concentration after nine days of fermentation. Essential amino acids namely; histidine, valine, methionine, isoleucine, as well as three non-essential amino acids like the aspartic acid, serine and proline were significantly improved in the fermented coconut-residue. The current findings suggested that fermented coconutresidue is a feasible source of protein and amino acids in feed formulation.